A new genus and species of gall midge (Diptera: Cecidomyiidae) inducing leaf galls on Peking lilac, Syringa reticulata subsp. pekinensis (Oleaceae), in China - Jiao, Ke-Long; Zhou, Xiao-Yi; Wang, Hao; Fu, Huai-Jun; Zhou, Da-Kang; Li, Jing-Bo; Xiong, De-Ping; Wang, Yuan-Hong; Bu, Wen-Jun; Kolesik, Peter (Zootaxa, 2020)
Larvae of a previously unknown species of gall midge were found causing large numbers of pustulate leaf galls on Peking lilac, Syringa reticulata subsp. pekinensis (Oleaceae), in parklands and street greenery in Beijing, China. Heavily galled leaves become senescent and fall off prematurely. The gall midge is named Pekinomyia syringae Jiao & Kolesik, its morphology is described and the COI mitochondrial gene and 12S ribosomal gene segments are sequenced. A new genus, Pekinomyia Jiao & Kolesik (Cecidomyiinae: Lasiopteridi), is erected for the new species. The new genus differs from other Lasiopteridi in the strongly sclerotized aedeagus and the lack of mesobasal lobes in the male terminalia and is not assigned to any known tribe.